PERENCANAAN LANSKAP KEBUN AGROMEDIKA HAMBARO (KAMARO) SEBAGAI OBJEK AGROWISATA TANAMAN OBAT - Anton Gunarto (http://arl.faperta.ipb.ac.id/, 2011)
District of Bogor have potential competitiveness indeveloping agrotourism farms, include farms with agriculture medicinal plants based. Hambaro Agromedicinal Farm (Kamaro) is one of demfarm land for medicinal plants production and cultivation, especially rhizome plants. The aim of this researchis to build a concept of production farms mechanism (Demfarm) which produce medicinal plants from Bogor, and as agriculture tourism activity (agritourism) farm. Demfarm concept, as agriculture medicinal farm, is a farm which produce rhizome medicinal plants which all the supporting plants in the farm are plant for medicalpurposes. Demfarm concept as agrotourism farm is an educative tourism farm for introducing people about cultivation, post harvest activity, producing process, and also medicinal plants profile and its benefits.